SMARTPHONE DAN KELUARGA (DETERITORIALISASI KELUARGA PEMAKAI SMARTPHONE DI KOTA SURAKARTA) - Yudatama, Satria (ISSN.2252-8407)
SMARTPHONE DAN KELUARGA  (DETERITORIALISASI KELUARGA PEMAKAI SMARTPHONE  DI KOTA SURAKARTA) Eri Satria Yudatama, Nurhadi dan Atik Catur BudiatiPendidikan Sosiologi Antropologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sebelas Maret, Surakarta satriaeri9@gmail.com ABSTRACT The era of globalization brings the world that is experiencing deterritorialization, a new face of meaning is shown because territorial existence does not survive in one location. Deterritorialization contains the fusion of cultural boundaries that exist within a society. Through the participatory of fieldwork, this study aims to understand the patterns of behavior and relationships among the family members embodied in the smartphone user family in Surakarta, which has relevance to the context of deterritorialization that appears in the current urban families. Family members are able to get out of the territory of the family room when they are inside the home of a family institution. This results in the dynamics and the creation of new spaces of "virtual space" and "consumption space" in family homes in Surakarta. On the other hand, there is a new scheme that can be evoked from the smartphone user's family case is the existence of negotiations or adjustments made by the family members through socialization and interaction within the family home of smartphone users.  Keywords: urban families, smartphone, socialization, interaction, deterritorialization